Economic Empowerment Management Mosque-Based Society At At-Takwa Mosque Pemangkat - Islani; Munadi; Deni Irawan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This study aims to answer two problems, namely how the strategy of the mosque in the empowerment of the Ummah konomi, how the advantages and disadvantages of the strategy of the mosque in the economic empowerment of the Ummah, and how the results of the strategy of the mosque in the economic empowerment of the Ummah. This research is a field research with qualitative descriptive approach. Data collection techniques using interviews, observations, documentation and literature studies, related to the strategy of the mosque at-Takwa Pemangkat in the economic empowerment of the people. The results showed that the strategy of economic empowerment of the people used by the at-Takwa Pemangkat mosque is to use two different empowerment programs, but the two programs are related to each other. Mosque cooperatives explore the potential possessed by pilgrims who want to open a business or add business and strive to develop their business, while LAZIS has a business development program for the poor or needy to empower from the economic side. The advantages of the at-Takwa Pemangkat mosque strategy in empowering the people's economy, namely resources, is a very important part in supporting a performance in the implementation of activities that are a good unity of Personnel potential (HR), availability of funds, and infrastructure support that can be utilized in implementing the economic empowerment of the people. Providing convenience for customers who want to borrow funds by providing guarantees in the form of family CARDS, marriage certificates etc. The weakness of the at-Takwa Pemangkat mosque strategy is the lack of human resources owned by the mosque so that it is not able to provide training and supervision to pilgrims who are given business capital. The result of the strategy of economic empowerment of the people that the micro-business actors who are given assistance from the mosque make their business more developed and influential on the economic welfare of the family. This book is a template for writers. All the necessary components of the journal such as title, abstract, introduction, and so on have been exemplified here. So it remains only to use it by stacking it. For example, the abstract is typed in a single paragraph of no more than 250 words, which contains the essence of the entire writing regarding the introduction and objectives, methods, research results in brief and conclusions, and follows the format as seen in this section. The entire journal is typed following this template with many pages of 8-12 pages. Abstract written in Indonesian and English.